2022
DOI: 10.1111/nyas.14844
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of machine learning approaches for structure–function modeling in glaucoma

Abstract: To evaluate machine learning (ML) approaches for structure-function modeling to estimate visual field (VF) loss in glaucoma, models from different ML approaches were trained on optical coherence tomography thickness measurements to estimate global VF mean deviation (VF MD) and focal VF loss from 24-2 standard automated perimetry. The models were compared using mean absolute errors (MAEs). Baseline MAEs were obtained from the VF values and their means. Data of 832 eyes from 569 participants were included, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Wong et al 41 compared several machine learning approaches for the estimation of MD from RNFL thickness. They obtain MAEdecr% rates up to 26% using gradient-boosted trees in an external test set, which is half of the MAEdecr% reported in the current study (54%).…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al 41 compared several machine learning approaches for the estimation of MD from RNFL thickness. They obtain MAEdecr% rates up to 26% using gradient-boosted trees in an external test set, which is half of the MAEdecr% reported in the current study (54%).…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al reported several machine learning models that used the RNFL thickness measurements to estimate the mean deviation (MD) and total deviation (TD) values of the 24-2 map [26]. In their comparative analysis, all models outperformed their proposed baseline.…”
Section: Visual Field Estimation With Artificial Intelligencementioning
confidence: 99%